Water treatment via filtration process - Muhamad, Mimi Suliza; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, Roslinda (Penerbit UTHM, 2020)
Water is important element for livelihood. About 71% of water covered the Earth surface with 96.5% is salt water, while the remaining 3.5% is fresh water for consumption [1]. The increased of population and urbanization had increase the demand for safe drinking water worldwide. The main challenges in producing potable water is the escalation of polluted water sources.